ASAL USUL DAN KARAKTERISTIK MADRASAH - Syafrizal, Syafrizal; Iswantir, Iswantir (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
The purpose of this discussion is the Origin and Characteristics of Madrasas. The type of research that the writer did was field research which is a qualitative description. Data collection techniques that the authors use are through observation, interviews, and documentation. The validity of the data used is triangulation. The analysis technique that the writer uses according to Miles and Huberman. Madrasas are a natural development of the mosque which in the early days of the Abbasid Caliphate (132 – 656 H/750 – 1258 AD) became the center for the development of Islamic education. That the madrasa that first appeared in the Islamic world and in the history of Islamic education was the nizamiyah madrasa founded by Nizam Al-Mulk, a Prime Minister (wazir) of the Seljuq dynasty during the reign of Alp Arselon and Sultan Malik Syah. The dominance of madrasas teaching the field of jurisprudence, George Makdisi (1981 AD) gave the name of the Nizamiyah madrasa as a college of law. ​Strategy and Prospects for the Development of Madrasas in the Islamic World, must be able to enhance the intelligence and abilities of students, advance science and technology along with its benefits and applications.